Dose–volume metrics and their relation to memory performance in pediatric brain tumor patients: A preliminary study. Issue 9 (1st June 2018) - Raghubar, Kimberly P.; Lamba, Michael; Cecil, Kim M.; Yeates, Keith Owen; Mahone, E. Mark; Limke, Christina; Grosshans, David; Beckwith, Travis J.; Ris, M. Douglas
Abstract: Background: Advances in radiation treatment (RT), specifically volumetric planning with detailed dose and volumetric data for specific brain structures, have provided new opportunities to study neurobehavioral outcomes of RT in children treated for brain tumor. The present study examined the relationship between biophysical and physical dose metrics and neurocognitive ability, namely learning and memory, 2 years post‐RT in pediatric brain tumor patients. Procedure: The sample consisted of 26 pediatric patients with brain tumor, 14 of whom completed neuropsychological evaluations on average 24 months post‐RT. Prescribed dose and dose–volume metrics for specific brain regions were calculated including physical metrics (i.e., mean dose and maximum dose) and biophysical metrics (i.e., integral biological effective dose and generalized equivalent uniform dose). We examined the associations between dose–volume metrics (whole brain, right and left hippocampus), and performance on measures of learning and memory (Children's Memory Scale). Results: Biophysical dose metrics were highly correlated with the physical metric of mean dose but not with prescribed dose. Biophysical metrics and mean dose, but not prescribed dose, correlated with measures of learning and memory. Conclusions: These preliminary findings call into question the value of prescribed dose for characterizing treatment intensity; they also suggest that biophysical dose has only a limited advantage compared to physical dose when calculated for specific regions of the brain. We discuss the implications of the findings for evaluating and understanding the relation between RT and neurocognitive functioning.